STUDY OF THE INDONESIAN COAL INDUSTRY DEVELOPMENT : INTER-INDUSTRY AND ECONOMETRIC APPROACHES - Achmadi Rosyid (NIM 221 04 016), Fadhila
Coal is one of the nonrenewable resources in Indonesia. It has important role for Indonesia. Due to its usage, as a source of energy and export commodity that produces income for Indonesia. Its nonrenewable characteristic raises a problem. After all resources are used, it will be exhausted. Meanwhile from the demand point of view, both domestic and international coal demand will keep on increasing. At one side, National Energy Policy is stipulated to replace oil with coal as an energy source that will definitely increase domestic coal demand. At the other side, high rate of international coal price will attract coal mining company to get winfall revenue by increasing the production capacity and exports. Based on the above explanation, it is required to optimize the national coal production based on conservation principles, so that coal can be used as an energy source for long term utilization. From the research that has been carried out, optimum result of coal mining production has not been achieved yet. It is shown from various indicators, such as: - Backward linkage for coal mining sector is 0,745. Meanwhile, forward linkage for coal mining sector is 0,768. It face linkage indices are less than 1, it is indicated that the coal mining sector can not be a part to develop other sectors in the Indonesian economy. - Based on energy intensity, it is shown that coal as one of the energy source can not optimize the economic growth. The energy intensity of Indonesia is 0,60 or less than 1,00 whereas the average energy intensity of the developed countries is 0,25. It is assumed that optimization in coal production is necessarily required. It can be carried out using economic growth instrumentation which is possible to converging Indonesian energy intensity to be at least the same as average Asia Pacific developed countries energy intensity of around 0,25. Several econometric equations that are developed to determine the convergence of Indonesian energy intensity (E) towards of the Asia Pacific developed countries are : (FORMULA) The result of forecasting shows that the possible percapita GDP growth to accomplish Indonesia energy intensity to be converge with the average Asia Pacific energy intensity is of 6.5% per year. By doing so, the convergence will be achieved in 2030. In order to reach 6.5% percapita GDP growth rate, the required coal production in 2020 is of about 346 million tonnes. However, if the coal production follows the current market mechanism, coal production in 2020 will be of about 456 million tonne. Anticipating the above conditions, several government policies needed in term of national coal resource management among others, are: - To promote incentives to be given to the mining company that is able to increase coal production target. - To develop sectors having close linkage with coal mining production. - To encourage for domestic coal utilization (domestic market obligation). - To develop some more exploration in order to increase coal reserves. - To develop policy for greater and deeper of low rank coal utilization.